Design of a robust active queue management algorithm based on feedback compensation. - Heying, Zhang (Computer communication review.)
Active Queue Management (AQM) is a very active research area in networking. The main objective of an AQM mechanism is to provide low delay and low loss service in best-effort service networks. In this paper we propose a new AQM algorithm based on the feedback compensation technique in control theory. The algorithm is called Proportional Integral based series compensation, and Position feedback compensation (PIP). By choosing the appropriate feedback compensation element and its parameters, the properties of the corrected system become dependent, to a great extent, on the series and feedback compensatory elements. Thus, PIP can eliminate the error incurred by the inaccuracy in the linear system model as well as eliminate the sensitivity to the changes in system parameters like load level, propagation delay, etc. The performance of PIP is compared to PI using ns simulations. From the experiments and analysis we conclude that PIP is more responsive to and robust under time-varying network conditions than PI.